Berat badan lahir rendah (BBLR) dengan kejadian stunting pada anak usia 6-24 bulan - Darwin Nasution; Detty Siti Nurdiati; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Stunting is one of the main problems of malnutrition often found in under-five children. The impacts include a delay in child’s growth, low endurance, lack of intelligence and productivity. The direct factors that influence the incidence of stunting are low birth weight (LBW) while the indirect factors are socioeconomic factors such as maternal education, low family income and a large number of family members.Objective: To analyze the relationship between LBW and the incidence of stunting in children aged 6-24 months in Yogyakarta Municipality.Method: This was a case-control study. The subjects were children aged 6-24 months with a group of cases comprising stunted children based on the indicator of height/age with a cut-off < -2 SD Z-score and the control group comprising normal children. The number of subjects for the study was 242 with the under-five children’s mothers as the research respondents. The sample selection used non-probability sampling with a consecutive sampling method. The data were analyzed by Chi-Square and multiple logistic regression.Results: The proportion of children 6-24 months who had low birth weight was 15.7 %. There was a significant relationship between LBW and the incidence of stunting in children aged 6-24 months (OR=5.60; 95%CI:2.27 to 15.70). There was a relationship between maternal height and the incidence of stunting in children aged 6-24 months (OR=2.14; 95%CI:1.08 to 4.33). Socioeconomic factors (maternal education, family income and a number of family members) did not have a significant relationship with the incidence of stunting.Conclusion: LBW had a relationship with the incidence of stunting in children aged 6-24 months in Yogyakarta Municipality.